2009
DOI: 10.1088/0964-1726/18/8/085011
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the primary anti-symmetric Lamb mode (Ao) with symmetric delaminations: numerical and experimental studies

Abstract: The interaction of an ultrasonic guided Lamb wave mode with delamination type defects in a quasi-isotropic laminated composite plate has been studied, using both simulations and experiments. In a laminated composite plate with a symmetric delamination, when the primary anti-symmetric mode, Ao, is incident at the entrance and exit of a delamination, it generates a new mode, So, that is confined only to sub-laminates and undergoes multiple reflections in the delaminated region. It was observed that only the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 16 publications
(26 reference statements)
2
90
0
Order By: Relevance
“…4a). The volumetric void method used in [21,23,39] was employed to describe delamination, that is to say, a node of the guided-wave model was split into two if it was located in the predicted delamination region, as illustrated in Fig. 5a.…”
Section: Damage Modelling and Transfermentioning
confidence: 99%
“…4a). The volumetric void method used in [21,23,39] was employed to describe delamination, that is to say, a node of the guided-wave model was split into two if it was located in the predicted delamination region, as illustrated in Fig. 5a.…”
Section: Damage Modelling and Transfermentioning
confidence: 99%
“…They showed that the A 0 Lamb wave is sensitive to the delamination at all through-thickness locations. Recently, Ramadas et al 13 investigated the A 0 Lamb wave interaction at a delamination located at the middle plane of a composite laminate. An experimentally validated 2D FE model was used to explain a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The wave modes will be affected by the delamination in different ways depending on its mode of vibration. In the literature (Grondel et al 2002;Su et al 2007;Hu et al 2008;Ramadas et al 2009;Rekatsinas et al 2015), the three fundamental wave modes S 0 , A 0 and SH 0 are the most studied and the most commonly used in order to interrogate a structure. The symmetric mode is chosen at low frequencies, below 200 kHz, because they are less dispersive so the shape of the pulse does not spread along the propagation direction which eases the post-analysis and reduce the complexity of the acquired signals.…”
Section: Damage Detectionmentioning
confidence: 99%
“…This wave mechanism is called mode conversion and it also occurs when the wave reaches the edge of a plate, so new wave modes are created and reflected backwards. Mode conversion in delaminations has been studied in several investigations in order to take advantage of these changes and use them to detect and locate these defects (Su et al 2007;Hu et al 2008;Ramadas et al 2009). Hu et al (2008) analysed numerically the propagation of the S 0 mode through a delamination.…”
Section: Damage Detectionmentioning
confidence: 99%